2019
DOI: 10.1097/phm.0000000000001185
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ankle-Foot Orthosis on Gait Efficiency in Ambulatory Children With Cerebral Palsy

Abstract: Objective Children with cerebral palsy experience functional limitations because of excessive muscle weakness, spasticity, and impaired motor control. They are prescribed ankle-foot orthoses to assist with ambulation. Our objective was to analyze stride length and dorsiflexion data comparing the effectiveness of “ankle-foot orthoses” with “barefoot or shoes only” on ambulatory children with cerebral palsy. Design An electronic literature search was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
0
8
0
2
Order By: Relevance
“…Even though an AFO is a frequently prescribed intervention for children with CP, rigorous evidence of their efficacy is limited [52], mainly because of the heterogeneity of outcome measures among researchers, which limits comparison between studies [53]. Although previous reviews have reported similar results and identified some of the limitations described above, still none have reported consistent guidelines for future studies [10,[21][22][23][24].…”
Section: Methodological Considerations Of This Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though an AFO is a frequently prescribed intervention for children with CP, rigorous evidence of their efficacy is limited [52], mainly because of the heterogeneity of outcome measures among researchers, which limits comparison between studies [53]. Although previous reviews have reported similar results and identified some of the limitations described above, still none have reported consistent guidelines for future studies [10,[21][22][23][24].…”
Section: Methodological Considerations Of This Reviewmentioning
confidence: 99%
“…Many studies involving orthotic use with CP patients present a wide variety of discrepancies in inclusion criteria or baseline assessments; missing information about orthosis design and construction, and how they are used; and different types of outcomes that can bias the indicated results. Previous systematic reviews have not focused on specific CP subgroups or referred to gait pattern classifications, thereby including a wide range of gait abnormalities, or have included the information of lower quality studies [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The reduced energy expenditure was found to be effective in improving stride length, speed of walking, single limb support, and gait symmetry; it also helped in decreasing energy expenditure of hemiplegic CP as compared with the barefoot condition. Further studies are required for better evidence regarding this [71].…”
Section: Atefehaboutorabi Et Al (2017)mentioning
confidence: 99%
“…Одним из важных составляющих комплексного биомеханического обследования пациентов с ДЦП является оценка пространственно-временных показателей ходьбы, что особенно актуально при оценке эффективности ортезирования. В частности, по данным ряда исследователей, использование ортеза на ГСС увеличивает скорость ходьбы [22,23,24] и длину шага [25,26,27]. По нашим данным, статистически значимое различие при использовании ортопедической обуви и ортезов на ГСС по сравнению с ходьбой босиком наблюдалось только по переменной длины шага правой нижней конечности.…”
Section: окончание таблицы 3 обсуждениеunclassified
“…Исходя из вышесказанного, обсуждение построено на основании указанных результатов. Так, данные, представленные в таблице 3, показали, что ношение AFO по сравнению с ходьбой босиком положительно влияет на пространственно-временные характеристики походки (длину и скорость шага) с различиями средних значений в диапазоне от 5,5 до 26,0%, в этом наши результаты согласуются с данными литературы [22,23,24,25,26,27]. Примечательно, что эти различия тем больше, чем тяжелее уровень нарушения глобальных моторных функций.…”
Section: окончание таблицы 3 обсуждениеunclassified